2011
DOI: 10.3727/096368910x524764
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mononuclear Cells Increase Retinal Ganglion Cell Survival and Axon Regeneration in the Adult Rat

Abstract: The central nervous system (CNS) of adult mammals generally does not regenerate, and many studies have attempted to identify factors that could increase neuroprotection and/or axonal outgrowth after CNS lesions. Using the optic nerve crush of rats as a model for CNS injury, we investigated the effect of intravitreal transplantation of syngeneic bone-marrow mononuclear cells (BMMCs) on the survival of retinal ganglion cells (RGC) and on the regeneration of optic axons. Control animals received intravitreal sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 56 publications
6
54
0
1
Order By: Relevance
“…This explanation can be supported by our previous observation that BMC treatment enhances glial cell proliferation and neuronal survival [5]. Interestingly, increased levels of FGF-2 with bone marrow cells therapy have also been reported in regenerating tissue in a model of optic nerve crush lesions [15]. …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This explanation can be supported by our previous observation that BMC treatment enhances glial cell proliferation and neuronal survival [5]. Interestingly, increased levels of FGF-2 with bone marrow cells therapy have also been reported in regenerating tissue in a model of optic nerve crush lesions [15]. …”
Section: Discussionsupporting
confidence: 56%
“…Several mechanisms have been suggested to explain how BMMC contribute to improve cell therapy following nerve injury [1,5,15,19,20]. Initial observations suggested that bone marrow multipotent stem cells could differentiate into any neural cell type depending on the environment conditions [21-24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell‐based therapy has been intensively studied. Different types of cells from diverse sources have been investigated for neuro‐repair after ON injury, including Schwann cells, fibroblasts, olfactory ensheathing cells, and bone marrow mononuclear cells . These cells can serve as biological mini‐pumps, releasing trophic factors to promote RGC survival and axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Following an optic nerve crush, many axotomized retinal ganglion cells die due to a lack of target-derived neurotrophic factors. But the delivery of bone-marrow mononuclear cells provides neuroprotection and increases both retinal ganglion cell survival and axon outgrowth 106. Similarly, mesenchymal stem cells transplanted into the rat brain reduce ischemia- induced brain damage in rats by inducing a marked increase in the synthesis of neurotrophic factors such as vascular endothelial growth factor, epidermal growth factor, and basic fibroblast growth factor in the host brain 107.…”
Section: Neuroprotectionmentioning
confidence: 99%